2004
DOI: 10.1073/pnas.0405262101
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of anisotropic energy transport in flowing polymers by using a holographic technique

Abstract: Almost no experimental data exist to test theories for the nonisothermal flow of complex fluids. To provide quantitative tests for newly proposed theories, we have developed a holographic grating technique to study energy transport in an amorphous polymer melt subject to flow. Polyisobutylene with weight-averaged molecular mass of 85 kDa is sheared at a rate of 10 s ؊1 , and all nonzero components of the thermal conductivity tensor are measured as a function of time, after cessation. Our results are consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
3
17
1
1
Order By: Relevance
“…Hence, the data shown in Figure 9 provide experimental evidence that supports the validity of the stress‐thermal rule eq 2 expressed as follows: D 11 − D 33 = D eq C t σ. The value of the normalized stress‐thermal coefficient from this figure is C t G N ≅ 0.014 ± 0.003, which is somewhat smaller than that observed for other crosslinked polymers34, 35 and polymer melts 29–33…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…Hence, the data shown in Figure 9 provide experimental evidence that supports the validity of the stress‐thermal rule eq 2 expressed as follows: D 11 − D 33 = D eq C t σ. The value of the normalized stress‐thermal coefficient from this figure is C t G N ≅ 0.014 ± 0.003, which is somewhat smaller than that observed for other crosslinked polymers34, 35 and polymer melts 29–33…”
Section: Resultscontrasting
confidence: 53%
“…Over the past 15 years, we have developed and implemented an FRS setup that allows for measurement of time‐dependent components the thermal diffusivity tensor D = k /ρ ĉ p in polymeric materials. This setup has been used to investigate anisotropic thermal conduction in polymer melts subjected to step and constant rate shear flows,29–33 in crosslinked elastomers subjected to uniaxial elongation,34, 35 and in quenched amorphous polymers 36. In these studies, the state of stress was also measured allowing for examination of the validity of the stress thermal rule.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the thermal conductivity of polymeric liquids is anisotropic under shear flows in general [26,27,28,29], and some experimental studies have reported that the linear stress-thermal relation between the stress tensor and thermal conductivity holds. [30,31,32,33] However, in the present study, we only consider the isotropic thermal conductivity as the first step because the effect of shear thinning of the viscosity is thought to be more crucial to viscous heating under strong shear flows than that of the anisotropy of the thermal conductivity.…”
Section: Problem and Methodsmentioning
confidence: 99%
“…(3b). Note that the thermal conductivity of polymeric liquids is anisotropic under shear flows, in general [29][30][31][32], and some experimental studies have reported that the linear stress-thermal relation between the stress tensor and thermal conductivity holds [33][34][35][36]. However, in the present study, we only consider the isotropic thermal conductivity as the first step because the effect of shear thinning of the viscosity is thought to be more crucial to viscous heating under strong shear flows than that of the anisotropy of the thermal conductivity.…”
Section: Problemmentioning
confidence: 99%